Virtual Communities and Covid-19: Has Social Media Informed a Sense of Belonging in Global Higher Education during the Pandemic? (Comparative & International Education Series, 2021)
A sense of belonging is typically derived from regular face-to-face contact with people and places. In global higher education it is often the case that students and staff will experience a profound sense of belonging and connection to their university and to their peers and colleagues within it. In a ‘new’ Covid-19 online landscape, this conceptual paper evaluates the position of networked publics as facilitators of belonging across global higher education during the pandemic. Learning communities, relationships and place attachments are discussed through the lens of social media. Through this, we determine whether global higher education has been strengthened by the communal expression and emotional support that networked publics facilitate. Issues such as student retention, digital accessibility and hybridised physical and virtual realities are also discussed.Keywords: belonging, communities, covid-19, place attachment, relationships, social media